Mass HIV treatment and sex disparities in life expectancy: demographic surveillance in rural South Africa - Bor, Jacob; Bärnighausen, Till (PLoS medicine, 2015)
Jacob Bor and colleagues use demographic data from a longitudinal surveillance cohort to identify increased gains in life expectancy among women compared to men in the years following antiretroviral therapy scale-up in rural South Africa.